Efficacy and Safety of Immune Checkpoint Blockades in the Treatment of Ocular Melanoma: A Systematic Review and Meta-Analysis - Zhao, Lu; Xia, Wenwen; Zhang, Yan; Zou, Peng; Zhu, Qiwen; Zhang, Rong (Frontiers in Oncology, 2021)
Aim: This meta-analysis aimed to compare the efficacy and safety of immune checkpoint blockade for the treatment of ocular melanoma. Methods: We searched the PubMed, EMBASE, and Cochrane Library databases up to July 2021. Effect sizes (ESs) and corresponding 95% confidence intervals (CIs) were used to compare the outcomes. Efficacy outcomes included complete response (CR), partial response (PR), stable disease (SD), progressive disease (PD), objective response rate (ORR), overall survival (OS), progression free survival (PFS). Safety outcomes included adverse events (AEs) and serious adverse event (SAEs). Results: A total of 16 eligible articles with 848 ocular melanoma patients were included. ICB treatment significantly improved CR (ES=0.02, 95%CI: 0.00-0.03, P=0.023), PR (ES=0.07, 95%CI: 0.05-0.09, P=0.000), SD (ES=0.31, 95%CI: 0.17-0.46, P=0.000), PD (ES=0.69, 95%CI: 0.61-0.77, P=0.000), ORR (ES=0.10, 95%CI: 0.04-0.15, P=0.000), OS (ES=9.68, 95%CI: 7.28-12.07, P=0.000) and PFS (ES=2.88, 95%CI: 2.69-3.07, P=0.000) in patients with ocular melanoma. Moreover, ICB therapies were associated with reduced AEs (ES=0.48, 95%CI: 0.30-0.67, P=0.000) and SAEs (ES=0.31, 95%CI: 0.18-0.45, P=0.000). Conclusions: ICB therapy showed good efficacy and safety in treating patients with ocular melanoma.